Mobile Learning for Special Preschool Education - Drigas, Athanasios; Kokkalia, Georgia (International Journal of Interactive Mobile Technologies (iJIM), 2016)
Nowadays the development of the Mobile Learning (ML) in children’s progress is thought significant. However, its role in special preschool education is recognized crucial, as it is a tool that can foster the knowledge and the experiences for this sensitive age. The support of specific areas in preschool education according to the educational perspective is thought significant with the maintenance of the mobile applications. In this paper we present a brief overview of the most representative studies of the last decade (2005-2015), which concentrates on skills that are examined in special kindergarten (early literacy, early mathematics, cognitive, social-emotional) and are supported by the mobile learning. The effectiveness of mobile applications in children who are autistic and face attention deficit problems is examined. The role of mobile learning in preschool children who face mental problems is also investigated.